Brown girls : a novel - Andreades, Daphne Palasi (Random House, 2022)
"This remarkable, deeply moving story brings you deep into the hearts and souls of a tight-knit group of friends--girls growing up in Queens, the polyglot borough of New York, where the streets sprawl for miles and echo with voices from all over the world, and the scent of bubbling oil, chopped garlic, and grilled meats waft through open windows as night comes to the neighborhood. Here Nadira, Mae, Trish, and Aisha become friends for life--or so they vow. Together they learn to survive all that the street throws at them--schoolyard bullies, clueless teachers, and the leering gaze of men who trail behind them wherever they walk. Exuberant and wild, they are daughters of immigrants from different diasporas, but in Queens their backgrounds blur and blend: they sing Mariah Carey at the tops of their lungs, pine for boyfriends who pay them no mind--and break the hearts of those who do--all while balancing the cultures they came from and the one they find themselves in. In small brick houses, their fathers snore on armchairs after long shifts, while mothers command them to be dutiful daughters, obedient young women. But as the years go by, and their own adulthood nears, choices must be made about their futures. Cracks and fissures form as some find themselves drawn to the allure of other skylines, beckoned by lovers and jobs foreign to what they knew back home. Some of the girls become wives and mothers to a new generation of brown girls; while others embark on a migration baffling to the generation before them, journeying back to the countries their parents fled for the 'better life' in America"--